MINAR1 is a Notch2-binding protein that inhibits angiogenesis and breast cancer growth. (2nd March 2018) - Ho, Rachel Xi-Yeen; Meyer, Rosana D; Chandler, Kevin B; Ersoy, Esma; Park, Michael; Bondzie, Philip A; Rahimi, Nima; Xu, Huihong; Costello, Catherine E; Rahimi, Nader
Abstract: Intrinsically disordered proteins (IDPs)/intrinsically unstructured proteins are characterized by the lack of fixed or stable tertiary structure, and are increasingly recognized as an important class of proteins with major roles in signal transduction and transcriptional regulation. In this study, we report the identification and functional characterization of a previously uncharacterized protein (UPF0258/KIAA1024), major intrinsically disordered Notch2-associated receptor 1 (MINAR1). While MINAR1 carries a single transmembrane domain and a short cytoplasmic domain, it has a large extracellular domain that shares no similarity with known protein sequences. Uncharacteristically, MINAR1 is a highly IDP with nearly 70% of its amino acids sequences unstructured. We demonstrate that MINAR1 physically interacts with Notch2 and its binding to Notch2 increases its stability and function. MINAR1 is widely expressed in various tissues including the epithelial cells of the breast and endothelial cells of blood vessels. MINAR1 plays a negative role in angiogenesis as it inhibits angiogenesis in cell culture and in mouse matrigel plug and zebrafish angiogenesis models. Furthermore, while MINAR1 is highly expressed in the normal human breast, its expression is significantly downregulated in advanced human breast cancer and its re-expression in breast cancer cells inhibited tumor growth. Our study demonstrates that MINAR1 is an IDP that negatively regulates angiogenesis and growth of breast cancer cells.